Unexpected Fluorescence of Polyols and PEGylated Nanoparticles Derived from Carbon Dot Formation. (16th October 2014) - Dong, Hailong; Roming, Marcus; Feldmann, Claus
<x xml:space="preserve">Abstract</x> Synthesis of nanoparticles in high‐boiling alcohols (so‐called polyol synthesis) and surface functionalization of nanoparticles with polyethylene glycol (so‐called PEGylation) in combination with certain heating are often accompanied with an intense fluorescence in the blue to green spectral range. Based on the polyol synthesis of Zn3(PO4)2 nanoparticles and a critical consideration of the relevant experimental conditions—including the presence of nanoparticles, the role of dissolved metal salts (ZnCl2, MgCl2, KCl), the type of the polyol (DEG, GLY, PEG400), the temperature and time of heating (150–230 °C, 1–6 h)—we can correlate the observed fluorescence to the formation of carbon dots (C‐dots) stemming from thermal decomposition (i.e., dehydration and carbonization) of the polyol. Thus, the thermal decomposition of polyols results in C‐dots with a diameter of 3–5 nm at narrow size distribution. The formation of C‐dots is confirmed by transmission electron microscopy (TEM), high‐resolution TEM (HRTEM), X‐ray powder diffraction (XRD), Fourier‐transform infrared spectroscopy (FT‐IR), and fluorescence spectra.